Comparative study of treatment interventions for patellar tendinopathy: a protocol for a randomised controlled trial - López-Royo, Maria Pilar (BMJ Open, 2020)
INTRODUCTION: Patellar tendinopathy is a degenerative disease of the patellar tendon, which affects athletes from a variety of sports, and is especially predominant in sports involving high-impact jumping. The aim of this study is to determine the additional effect of two interventions combined with eccentric exercise and compare which one is the most effective at short-term and long-term follow-up for patients with patellar tendinopathy. METHODS AND ANALYSIS: This study is a randomised controlled trial with blinded participants. Measurements will be carried out by a specially trained blinded assessor. A sample of 57 patients with a medical diagnosis of patellar tendinopathy will participate in this study and will be divided into three treatment groups. Eligible participants will be randomly allocated to receive either: (a) treatment group with percutaneous needle electrolysis, (b) treatment group with dry needling or (c) treatment group with placebo needling. In addition, all groups will perform eccentric exercise. Functionality and muscle strength parameters, pain, ultrasound appearances and patient perceived quality of life shall be evaluated using the Victorian Institute of Sports Assessment for patellar (VISA-P), jump tests, Visual Analogue Scale, ultrasound images and Short Form-36 (SF-36), respectively. Participants will be assessed at baseline, at 10 weeks and at 22 weeks after baseline. The expected findings will allow us to advance in the treatment of this injury, as they will help determine whether a needling intervention has additional effects on an eccentric exercise programme and whether any of the needling modalities is more effective than the other. ETHICS AND DISSEMINATION: This protocol has been approved by the Ethics Committee of Aragon (N° PI15/0017). The trial will be conducted in accordance with the Declaration of Helsinki. TRIAL REGISTRATION NUMBER: NCT02498795